THE TAX-SPEND DEBATE – REVIEW OF THE EMPIRICAL LITERATURE - Tashevska, Biljana (Ss Cyril and Methodius University in Skopje, Faculty of Economics - Skopje, 2018)
This article reviews the empirical literature on the “tax-spend debate” or “revenue-expenditure nexus” that emerged in mid 1980s due to concerns over budget deficits. This strand of literature examines the intertemporal relationship between government revenues and government expenditures in the generation of budget deficits. Several observations can be made based on the literature survey: there is insufficient research on less developed and transition countries; not many studies that confirm the tax-spend hypothesis report whether the Friedman (1978) or Buchanan-Wagner (1977) versions is supported; few studies elaborate on the institutional setting in the countries, the key legislation or any specifics of the budgetary process, which all influence the fiscal outcomes; there is an increasing use of non-linear approaches, which allow for a shift in the fiscal behaviour and in the sustainability of the fiscal budget depending on whether an economy is above or below some threshold estimate; there is a much scarcer literature on the tax-spend debate on a subnational level, compared to the national level.
Keywords: tax-spend debate, government revenues, government expenditures, revenue-expenditure nexus, Granger causality